Globalization and the transitional cultures : an eastern perspective - Nag, Debanjana, Dr (Diverse perspectives on creating a fairer society., 2024)
Globalization has quickened the process of communication across the world, creating changes in material and non-material culture with the flow of ideas. Globalization and the Transitional Cultures: An Eastern Perspective takes different cases from various perspectives, such as gender, modernity and the middle-class, to understand the impact of globalization on Eastern societies. Globalization and the Transitional Cultures: An Eastern Perspective engages with a range of diverse themes that are shaping cultural discourses, especially in developing nations like India. Debanjana Nag debates the ideological and rational growth of globalisation as a fuel of modernity and analyses the perspectives of marginalized sections of society such as women, tribes and the middle-class society who are at the highest in terms of economic concentration. She also discusses concepts of globalization, communication, and culture to understand how communication plays an important role in the process of globalization for various cultural realms. Nag brings together a wide range of concepts that describe the complexity of the globalization question and its impact on profound societal processes.